2019
DOI: 10.1007/s11266-019-00102-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Charity Begin at Home? National Identity and Donating to Domestic Versus International Charities

Abstract: Despite the increased social significance currently attached to national identity, little is known about how national group attachment may correlate with the decision to donate to domestic versus international charities. The current study brings together literature on national identity and charitable giving to empirically validate a model of charitable ethnocentrism and cosmopolitanism. The substantive study is based on an online survey administered to a sample of 1004 UK respondents. The findings indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…The negative effect is in line with previous consumer research showing that ethnocentric tendencies demotivate behaviors that benefit the outgroup (Shankarmahesh, 2006). Furthermore, we extend Hart and Robson's (2019) research on charitable ethnocentrism. In addition to this study, we provide empirical evidence that an individual's ethnocentric disposition has a negative influence on international donation intention.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The negative effect is in line with previous consumer research showing that ethnocentric tendencies demotivate behaviors that benefit the outgroup (Shankarmahesh, 2006). Furthermore, we extend Hart and Robson's (2019) research on charitable ethnocentrism. In addition to this study, we provide empirical evidence that an individual's ethnocentric disposition has a negative influence on international donation intention.…”
Section: Discussionsupporting
confidence: 90%
“…To date, the effect of ethnocentrism on giving behavior remains largely unexplored, except for a recent study by Hart and Robson (2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, research has indicated that small local charities are more trusted by the public than larger charities (Hart & Robson, 2019; O'Loughlin‐Banks & Raciti, 2014). Moreover, the area of activity of a charity has been shown to influence the level of public trust.…”
Section: An Outline Research Agendamentioning
confidence: 99%
“…Some studies have looked at determinants of individual cross-border giving. These studies include why people give to causes/countries far from home (Appe & Oreg, 2020;Casale & Baumann, 2015;Grimson et al, 2020), the influence of national identity (Hart & Robson, 2019), and how repressive NGO environments influence donor giving (Chaudhry & Heiss, 2020). Other studies have attempted to measure cross-border philanthropy flows within a limited context such as corporate foundations and philanthropy (Hornstein & Zhao, 2018;Seo et al, 2018), diaspora philanthropy (Baker et al, 2007;Carpi & Fiddian-Qasmiyeh, 2019;Newland et al, 2010), and the interaction between governments and the civil sector (Ibrahim, 2015;Oelberger & Shachter, 2020).…”
Section: Introductionmentioning
confidence: 99%